Enhancing Green Waqf For Carbonization Technology: Opportunities for Sustainable Development Goals (SDGs) in Indonesia - Hasan, Nurul Fatma; Syahruddin, Syahruddin (El-Barka, 2022)
Introduction/Main Objectives: Green economy, a new concept of combating global warming and climate change through economic activities, becomes a prominent theme for politicians, scientists, activists, and businessmen. The main purpose of this research is to propose green economy by enhancing green waqf for Carbonization Technology. Background Problems: Waste countinuos to be one of the major problems facing the stable development of the economy and society. Managing waste is needed to reduce environmental damage and provide benefits for all. Novelty: Proposing green waqf for carbonization technology is a new concept. Research Methods: This research used qualitative approach by studying related literatures. Finding/Results: The results show that green waqf is strongly recommended to support green economy. Waqf as a charitable institution in Islam is expected to play its significant role to carry out environmental protection. Environmental protection could be achieved by waste management. Waste management by Carbonization Technology could supply renewable power and plays a crucial role in preserving the environment, improving living standards, and accelerating economic power. Conclusion: Enhanching green waqf for Carbonization Technology should be a prioritized program to support green economy. Hopefully, this is in line with SDG 7 (sustainable energy), SDG 11 (sustainable cities and communities), and SDG 13 (climate action).